ACQUISITION OF PASSIVE VOICE BY CHINESE LEARNERS OF PORTUGUESE AS A SECOND LANGUAGE - Li, Qunying (2021)
The passive voice is a verbal category whose full acquisition raises many difficulties for Chinese learners. The present work intends to study the interlanguage of 24 Chinese late learners of Mandarin L1 learners with basic Portuguese proficiency level, in order to find out if and in what way L1 transfer occurs at the syntactic level during the Portuguese second language acquisition process (PL2). Hence, two linguistic tasks, a grammaticality judgment task with correction and a Chinese to Portuguese translation task, were conducted, which allows to conclude: i) there is persistent negative transfer of L1 both in passive formation as in the syntactic domain; ii) the Chinese learners' interlanguage shows an incomplete acquisition verified through the omission of the auxiliary verb “ser”, which does not exist in Chinese; iii) as for the topic constructions and other syntactic particularities, the learners demonstrate more failures at the syntactic level, in spite of having consistent awareness about the use of the passive; iv) Chinese passive markers such as “bei” can evoke the use of passive in Portuguese, thus resulting in positive transference of the L1.